(3GdJShjb h EOGQI GdGYdGf (B/s - (3TheGf, GjfGS QGaJs ((3YeGf(B: s (3OGQ GdacQ(B, s, 2009)
(3eaghe GdGSJQGJjLjI h GdNWW GdJShjbjI , GdGYdGf h GdUfGYI GdGYdGfjI , SjGSGJ GdGSJQGJjLjI GdJShjbjI cgOa ddJNWjW GdGYdGfj , GSJQGJjLjI GdQSGdI GdGJUGdjI GdGYdGfjI , GSJQGJjLjI LOhdI h Jbjje GdMedI GdGYdGfjI C GSJQGfjLjIJMOjO GdeNUUGJ GdGLeGdjI ddMedI GdGYdGfjI (B.s
(3eQGLY U(B.289s
Keywords: (3COGQI GdeHjYGJs; (3GdGYdGfs; (3GdJQhjLs; (3GdJShjbs